Factors Affecting Mode of Birth in Women With Preexisting Diabetes and Gestational Diabetes: A Retrospective Cohort at a Tertiary Referral Center - Theresa Reischer; Sina Prossinger; Anja Catic; Eibhlin Healy; Christian Göbl; Gülen Yerlikaya-Schatten (Journal of Diabetes Research)
Women with preexisting diabetes and gestational diabetes mellitus (GDM) are at higher risk for adverse maternal and neonatal outcomes. However, there is no consensus on a uniform approach regarding mode of birth (MOB) for all forms of diabetes. The aim of the study is to compare MOB in women with preexisting diabetes and GDM and possible factors influencing it. A retrospective cohort study of women with GDM and preexisting diabetes between 2015 and 2021 at a tertiary referral center was conducted. One thousand three hundred eighty-five singleton pregnancies were included. One thousand twenty-two (74.4%) women had a vaginal birth (VB) and 351 (25.6%) a caesarean section. Preexisting diabetes was significantly associated with caesarean section compared to GDM (OR 2.43). Five hundred fifty-one (40.1%) women underwent induction of labor, and 122 (22.1%) women had a secondary caesarean after IOL. Women induced due to spontaneous rupture of membrane (SROM) achieved the highest rate of VB at 93%. The lowest rates of VB occurred if indication for induction was for preeclampsia or hypertension. IOL was significantly less successful in preexisting diabetes with a VB achieved in 56.4% for type 1 diabetes and 52.6% of type 2 diabetes compared to GDM (78.2% in GDM; 81.2% in IGDM; OR 3.25, 95% CI 1.70–6.19, p<0.001). The rate of VB was higher who were induced preterm compared to women with term IOL (n=240 (81.9%) vs. n=199 (73.2%); p<0.05). Parity, previous VB and SROM favored VB after IOL, whereas preexisting diabetes, hypertension, and IOL after 40+0 weeks are independent risk factors for caesarean delivery.